Effects of increasing molybdenum under low nitrogen input on yield, nitrogen-metabolizing enzymes and nitrogen use efficiency of winter wheat cultivars - Di Yang; Qixia Wu; Youning Wang (PLoS ONE, 2026)
In wheat production, improving resource utilization and grain yield has been a longstanding goal that researchers have been pursuing. This study aimed to investigate whether regulated nitrogen (N) and molybdenum (Mo) fertilizer management could enhance wheat yield and nitrogen use efficiency (NUE). This study reports the effects of three N application levels (N0: 0 kg N ha −1 , N1: 75 kg N ha −1 , N2: 150 kg N ha −1 ) and a combination of three Mo application levels (Mo1: 0 kg Na 2 MoO 4 ha −1 , Mo2: 0.75 kg Na 2 MoO 4 ha −1 , Mo3: 1.5 kg Na 2 MoO 4 ha −1 ) on N metabolism, NUE, and yield in wheat. The results showed that average grain yield increased by 61.78% under the different N input, and 11.71% under the different Mo input levels. Nitrogen agronomic efficiency (NAE), nitrogen recovery efficiency (NRE) and partial factor productivity (PEPN) significantly (P < 0.01) increased at the low N rates (N1) but significantly (P < 0.05) decreased at high N rates (N2). NAE and PEPN were significantly (P < 0.01) different among different Mo input levels. NAE significantly decreased with the increasing Mo input. Conversely, PEPN increased with increaseing Mo input, the N1 + Mo3 had the highest PEPN.With the increase of Mo, the leaf area index and net photosynthetic rate increased significantly at all growth stages. Compared with Mo1, the leaf area index (LAI) of Mo2 and Mo3 increased by 13.68% and 19.33%, respectively, and the photosynthetic rate increased by 26.47% and 45.07%. Compared with Mo0(control), NR, GS and GOGAT increased by 1.15%, 4.60%, and 1.95% in N1 and by 3.80%, 7.31%, and 4.94% in N2, respectively. We conclude that high Mo and low nitrogen input could prolong the duration of green leaves, enhance the activity of nitrogen metabolism enzymes during the middle and late growth stages, and improve spikelets number per spike and N metabolism, thereby having potential to increase wheat yield and NUE.